Enhancing autophagy mitigates LPS-induced neuroinflammation by inhibiting microglial M1 polarization and neuronophagocytosis - Jingjing Guo; Jingjing Guo; Yun Li; Kun Ma; Kun Ma; Guohai Su; Guohai Su (Frontiers in Cellular Neuroscience)
BackgroundAutophagy, a regulator of inflammation, has been implicated in various central nervous system pathologies. Despite this, the role and mechanisms of autophagy in lipopolysaccharide (LPS)-induced neuroinflammation are not clear. This study investigated whether autophagy can play a neuroprotective role in LPS-induced neuroinflammation.MethodsPrimary microglial cells and male C57BL/6 J mice were treated with LPS, autophagy inhibitors (3-methyladenine, 3-MA), or autophagy activators (rapamycin). Cell viability, NF-κB pathway activation, pro-inflammatory cytokine expression, M1 polarization, autophagy markers, and neuronal damage were evaluated via various techniques including CCK-8 assay, Western blot analysis, ELISA, immunohistochemistry, and histological staining.ResultsLPS (1 μg/mL) effectively inhibited cell viability, stimulated the expression of IκB-α and NF-κB, and simultaneously suppressed autophagy protein expression. The pro-inflammatory cytokines IL-1β and IL-6 showed a significant increase. Contrary to the effect of 3-MA, the rapamycin treatment inhibited the polarization of microglia cells to the M1 type in the various groups of microglia cells after LPS stimulation. This was evidenced by decreased expression of cytokines IL-1β, IL-6, and CD86, and increased expression of Arg-1, IL-10, and CD206. In vivo experiments found that mice with injections of LPS and 3-MA in the lateral ventricle showed significantly increased expression of IκB-α and NF-κB in brain tissues, elevated levels of pro-inflammatory cytokines, decreased autophagy levels, and increased necrotic neurons. There was increased aggregation of microglia cells and increased neuronophagocytosis. Conversely, mice injected with rapamycin showed enhanced neuronal cell autophagy, decreased expression of pro-inflammatory cytokines and apoptosis, and reduced neuronophagocytosis.ConclusionEnhancing autophagy can effectively mitigate LPS-induced neuroinflammation by inhibiting microglial M1 polarization and neuronophagocytosis, thereby protecting neuronal integrity. These findings suggest potential therapeutic strategies targeting autophagy in neuroinflammatory conditions.